Impact of attachment and traits of psychopathy on addictive behaviors of adolescents - Silva, Ana Rita; Relva, Inês Carvalho; Simões, Alice Margarida (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
The present study examines the relationship between substance use (measured by DAST), parenting and peer grouping (as measured by IPPA-R) as well as a set of psychopathic traits (assessed through the YPI-RE). The sample consisted of 317 adolescents who attended public schools in the northern region of the country. The results suggest a predictive effect of the traits of psychopathy in adolescent drug use. They also suggest a higher average consumption for adolescents between 15 and 18 years of age, and the analyzes did not reveal significant differences in consumption relative to the adolescent sex. They also suggest a negative correlation between drug use and the dimensions of the attachment evaluated.